1999
DOI: 10.1103/physrevb.59.7285
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent surface phonon mode of CdSe quantum dots

Abstract: The surface phonon mode of CdSe quantum dots in a glass matrix was investigated by Raman spectroscopy. The blueshift and broadening of the surface phonon frequency were observed as the quantum dot size was reduced. It was shown that the observed size-dependent blueshift and broadening are mainly caused by the lattice contraction and the boundary relaxation, respectively. ͓S0163-1829͑99͒00811-5͔

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
124
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 16 publications
24
124
0
Order By: Relevance
“…At the lowest temperatures, the bandwidth reflects the inhomogeneous distribution ⌫ inh , resulting from small variations in size, shape, or local environment of the NCs. The band broadening with rising temperature in semiconductor NDs was explained by scattering with acoustic and optical phonons [19][20][21][22] and, following Refs. 20 and 21 the total linewidth can be described as the sum of three terms,…”
Section: Temperature Effects On the Spectral Properties Of Colloidal mentioning
confidence: 99%
“…At the lowest temperatures, the bandwidth reflects the inhomogeneous distribution ⌫ inh , resulting from small variations in size, shape, or local environment of the NCs. The band broadening with rising temperature in semiconductor NDs was explained by scattering with acoustic and optical phonons [19][20][21][22] and, following Refs. 20 and 21 the total linewidth can be described as the sum of three terms,…”
Section: Temperature Effects On the Spectral Properties Of Colloidal mentioning
confidence: 99%
“…It is shown that the decrease of the nanocrystal concentration leads to the intensity decrease of the above mentioned bands, while the decrease of the nanocrystal size additionally leads to the low-frequency shift of the band formed by the Е and F 2 symmetry vibrations (Figs 2 and 3). It should be noted that in nanometric crystals the low-frequency shift of Raman bands and their broadening are most often explained by confinementrelated selection rules violation due to the small crystal size [15] and surface phonon modes [16]. In our case, the former factor seems to be hardly possible, because the minimal nanocrystal size studied here (15 nm) is, according to the calculations in [17], too big to ascribe the observed features of the size-related behaviour of the Raman band parameters to the phonon confinement.…”
Section: Resultsmentioning
confidence: 99%
“…A considerable low-frequency shift of the Raman bands and their broadening occurring in nanometric crystals are most often explained by confinement-related relaxation of selection rules due to small crystallite sizes [16] and surface phonon modes [17]. The former factor seems to be hardly possible in our case because, according to the calculations [18], the minimal crystallite size under studies (15 nm) is too large to ascribe the observed features of size-related behaviour of the Raman band parameters to phonon confinement.…”
Section: Resultsmentioning
confidence: 99%